Profile of PD-L1 mRNA Expression in Childhood Acute Leukemia - Azhar, Muhammad Al; ., Chainurridha; Aisyi, Mururul (Asian Pacific Journal of Cancer Biology, 2021)
Background: Programmed Death Ligand 1 (PD-L1) expression was used to determine type of patients who respond to immunotherapy using immune checkpoint inhibitor in several solid malignancies. However, the role of PD-L1 in hematological malignancies is less explored. Therefore, we aim to investigate PD-L1 mRNA expression in childhood leukemia patients. Association between PD-L1 expression and clinicopathological features was also analyzed. Method: Blood samples of 17 childhood leukemia patients and 12 healthy individuals as control were used in this study. The samples were collected in Dharmais Cancer Hospital. Real time PCR was used to analyze PD-L1 expression with GAPDH as internal control. Result: PD-L1 mRNA expression is significantly lower in childhood leukemia patients (medians: 0.0012) compared to healthy individuals (medians: 0.0041) (p=0.017). PD-L1 mRNA expressions were not correlated with age (p=1.000), sex (p=1.000), outcome (p=1.000), type of leukemia (p=1.000), hyperleukocytosis (p=1.000), and syndrome down (p=0.426). Conclusion: PD-L1 expression is lower in leukemia patients compared to healthy controls. PD-L1 expressions were not correlated with all clinicopathological features. Our result provides preliminary data of PD-L1 expression in Indonesian childhood leukemia patients.